2015
DOI: 10.1260/1747-9541.10.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Top-Level Judo Coaches on Training and Performance

Abstract: The main goal of this project was to assess top-level judo coaches' perceptions on two capital elements in coaching: training and competition management. 41 experienced, high-level coaches from Europe, Asia and America agreed to participate. An open-ended questionnaire was selected as the assessment instrument. The two main topics (training and competition) were divided in two areas: methodology and access to high-level performance, and combat strategies and coaches' roles and tasks during combat, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 22 publications
1
32
1
4
Order By: Relevance
“…This should facilitate the establishment of close interpersonal relationships between coaches and athletes (Purakhin, 2013), which has a positive effect on the process of preparing for a competition. However, it should be noted that foreign experts is encouraged to give the quality of training of trainers as much attention as the quality of the preparation of elite athletes (Santos, Fernandez-Rio, & Callan, 2015). It should be admitted that in this area is revealed a significant lack of research in the Russian Federation.…”
Section: Resultsmentioning
confidence: 99%
“…This should facilitate the establishment of close interpersonal relationships between coaches and athletes (Purakhin, 2013), which has a positive effect on the process of preparing for a competition. However, it should be noted that foreign experts is encouraged to give the quality of training of trainers as much attention as the quality of the preparation of elite athletes (Santos, Fernandez-Rio, & Callan, 2015). It should be admitted that in this area is revealed a significant lack of research in the Russian Federation.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it was revealed that among the coaches there is no consensus about the preferred BP models and the specialists structure training programs are based on the individual preferences (Tavares Junior, & Janotta Drigo, 2017). Furthermore, the high-level coaches believe that in order to achieve high performance training impact in judo should take into account the specifics of the competition (Santos, Fernandez-Rio, Almansba, et al, 2015). However, the modern judo is characterized by a high level of motor skills in the competitive matches.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of leading judo coaches carried out by L. Santos show that, according to world-class experts, anyone with the intention of winning a medal at a European or World Championship, or the Olympic Games, must be capable of conducting 6 different fighting techniques from a standing position and 2 in ground fighting. The main winning factors for athletes were defined as: dynamism, counterattacks, combination techniques, and adaptability to the rival's moves (Iermakov, et al, 2016;Santos, Fernandez-Rio, Almansba, Stercowicz, & Callan, 2015;Zubitashvili, & Mayashvili, 2012).…”
Section: Methodsmentioning
confidence: 99%